A Novel 2DOF Fractional Controller for Wind-Solar Integrated Power System - Majahar Hussain Mahammad; Ch Ravi Kumar (IAES Indonesian Section, 2022)
Power system is an integration of many power generating units with continuous load variation due to which the frequency of the power system changes. Using traditional proportional integral (PI) controllers, frequency transients are reduced, and with sufficient time delay zero steadystate error is obtained. In this proposed research article, a three-area thermal plant system with wind and solar photovoltaic power generating systems is considered. This integration of renewable system will lead to the frequency transients which has to be addressed seriously. To improve the frequency profile of this diverse-source interconnected power system, a novel two degree of freedom proportional fractional integral double derivative (2-DOF-PFIDD) controller is proposed. The integral square error (ISE) cost function is utilized to discover the best parameter gains of the proposed controller using the intelligent water drops algorithm (IWDs). The benefits of the proposed controller are evaluated using an IEEE-39 bus system with wind and solar photovoltaic (SPV) generation. Uncertainties in the wind and solar power system characteristics such as wind speed and irradiance are considered. Comparisons with typical proportional integral derivative (PID), two degree of freedom proportional integral derivative (2-DOF PID), and 2-DOF-PIDD controllers are presented to demonstrate the efficacy of proposed controller for improving the frequency and tie-line power profiles.